PV Inverter with Decoupled Active and Reactive Power Control to Mitigate Grid Faults. Issue 1 (March 2021) - Talha, M; Raihan, S. R. S.; Rahim, N.A.
Abstract: Low power distributed Photovoltaic (PV) systems would be a dominant power generator in future grids. This PV penetration significantly influence the grid stability, especially in an event of grid faults. Traditional PV inverters disconnect themselves from grid on detecting a low voltage at their point of common coupling (PCC). A temporary low voltage grid fault can lead to outage, if PV inverters are not equipped with low voltage ride through (LVRT) feature. During a low voltage grid fault PV inverter can assist the grid recovery process by not only staying connected to grid but also injecting reactive power into the grid. Many grid code standards have issued guidelines to inject reactive power during a low voltage fault. Development of low voltage ride through inverters require decoupled power flow control. In addition to maximum power point operation and standardized current injection to the grid, modern PV inverters should be able to deal with LVRT and loss of grid (LoG) ride through features, as demanded by the regulating grid codes. Reduction in grid outages can be achieved, if the PV inverters stay connected during LVRT, LoG and short circuit faults. Most of previous studies on LVRT control of PV inverters have not short circuit faults and loss of grid faults at PCC. This work proposed a PV inverter controller capable of controlling complex power into the grid. A decoupled current regulator with feed forward compensation is modelled. A short circuit grid fault is also tested with the developed PV inverter. It is found that the PV inverter ride through the low voltage and short circuit faults. The system is simulated in MATLAB(Simulink), the designed controller can provide decoupled active and reactive power to the grid during the fault events.